Many-channel microscopic cluster model of 8Be: Formation of high-energy resonance states - Zhaba, Vasyl; Lashko, Yuliia; Vasilevsky, Victor (Physical Review C, 2025)
The nature and structure of high-energy resonance states in 8Be, located just below and above the p + 7Li threshold, are investigated in detail. A microscopic many-cluster and many-channel model is employed to study the formation of these resonances. This model includes three distinct three-cluster configurations: 4He + 3H + p, 4He + 3He + n, and 4He + d + d, enabling a comprehensive treatment of all major binary decay channels of 8Be, namely 4He + 4He, p + 7Li, n + 7Be, and d + 6Li. The primary focus of our analysis is the structure and dominant decay channels of the twin 1^+, 2^+, 3^+, and 4^+ resonance states. Additionally, we propose and implement a model to clarify how the 2^+ resonance states lying below the p + 7Li threshold are formed. We demonstrate that these resonances are Feshbach-type states arising due to coupling of the open 4He + 4He channel with the closed channels p + 7Li, n + 7Be, and d + 6Li at these energies. Overall, the present approach provides a realistic description of the experimentally observed resonance spectrum near the 7Li + p decay threshold, including negative-parity states 1^- and 2^-.